Discussions of financial education among higher education students of the administration, accounting and economic sciences courses of two Public Universities (Research, Society and Development, 2022)
Financial education provides a better coexistence with money, making people citizens more prepared for the events of the economic system and more capable of evaluating trade offs. The main objective of this work is to identify the applications of financial education for students of administration, accounting and economic sciences at the Universidade Estadual da Paraíba and Universidade Federal de Campina Grande. The research is classified as quantitative and descriptive, with a sample of 141 students. For data collection, a closed questionnaire was used, available via Google Forms and sent on the courses' social networks. The data obtained were organized, tabulated and analyzed in Microsoft Excel spreadsheets. Among the results, it is possible to notice that the students of the three courses have very similar profiles, both in terms of classification of their profiles, with the majority of students employed at private institutions, without children and salaries between R$ 1,210.01 to R$ 1,210.01. 2,000.00, as well as in financial education applications, such as the possession of an emergency reserve, cash flow control and cost cutting among students. At the end of the work, it is concluded that the students of the analyzed courses apply financial education.